Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

From the Helpdesk: Observations and guidance on educational response planning during the COVID-19 crisis (EdTech Hub, 2020)
Written by Rachel Chuang, Tom Kaye, Caitlin Moss Coflan & Arjun Upadhyay (EdTech Hub Helpdesk Management Team) Amid one of the biggest global disruptions to schooling in living memory, countries are quickly developing distance education responses for students. The EdTech Hub’s Helpdesk is providing evidence-informed responses to requests for support from governments and their partners as they face this challenge. …
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707838 2405685:84ZQF884
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Education during the COVID-19 crisis: opportunities and constraints of using EdTech in low-income countries - David, Raluca; Pellini, Arnaldo; Jordan, Katy; Philips, Toby (Zenodo, 2020)
Key points: Technology can help mitigate the effects of the educational crisis and closures of schools, but ed-tech is not a silver bullet and governments need to have realistic expectations about what it can achieve The digital divide means that internet and mobile network access varies greatly in middle- and low-income countries Governments can provide immediate support by informing teachers about simple grassroots platforms where they can share their own ed-tech solutions Educational TV and radio broadcasts in combination with SMS are effective communication channels between educators and students when the internet connectivity is poor or not available It will be important for education authorities to begin planning how in 12-months’ time they will diagnose and treat the learning gaps that have emerged during the crisis.
shortDOI: 10/ghgnd7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3750976 10/ghgnd7 2339240:3CKN9C4K 2339240:5AHKKQF6 2405685:92ZVGWNU 2405685:CT8JMZEU
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodoETH; covid-19; crisis education; distance education; education; education policy; educational technology; emergency education; pandemic education; school closures; schools

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
ZenodoArchiveID: 3744581 previousshortDOI: 10/ghgng7 previousDOI: 10.5281/zenodo.3744581 EdTechHub.Source: 2405685:2WY8H4WW EdTechHub.Source: <this> shortDOI: 10/ghgng7 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3744581 10.5281/zenodo.3744581 10.53832/edtechhub.0021 10/ghgng7 2129771:QEIBUIQH 2339240:3NRFPYGI 2339240:TK94XQR9 2339240:XJRI6FW3 2339240:Y635S3D4 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:2WY8H4WW 2405685:6FFSC2Z8 2405685:DI4SGTPH 2405685:FLHI5BHC 2405685:FVE6PDBB 2405685:GG9HHSDL 2405685:PXAIRTEK 2405685:RLBPSG29
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
previousDOI: ​10.5281/zenodo.4299931 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4299931 10.5281/zenodo.4768560 2339240:CYPLQHH4 2405685:C49UMTX2 2405685:CWRFU9K9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652130 previousZenodoArchiveID: 3830953 previousshortDOI: 10/ghgk68 previousDOI: 10.5281/zenodo.3830953 shortDOI: 10/ghgk68 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3830953 10.53832/edtechhub.0033 10/ghgk68 2339240:XCBTX2XL 2405685:2HM2SBVM 2405685:FU7Z8QM7
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652140 previousZenodoArchiveID: 3936687 previousshortDOI: 10/ghgnd2 previousDOI: 10.5281/zenodo.3936687 shortDOI: 10/ghgnd2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3936687 10.53832/edtechhub.0037 10/ghgnd2 2339240:EHTSKIBR 2339240:YQHNWNMB 2405685:5P5HVP47 2405685:BBP57X2K 2405685:SKFMQF3F 2405685:XI5PXVB3
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:X5MR76ZW 2405685:29U93GQF